Sensory processing disorder and impairments in the learning processo of students with autismo spectrum disorders: A message for teachers (Research, Society and Development, 2020)
The learning and development of the child with Autism Spectrum Disorder (ASD) is linked to several situations that involve the psychological, physical, emotional and structural functions of human development. One of them is related to Sensory Processing Disorder which can impair the learning of children with ASD. For learning to take place, with the expected quality, in addition to other factors, it is necessary to harmonize the information that reaches the brain and turns into expected adaptive responses. When this process does not occur with quality, unsatisfactory responses are generated; there is, then, sensory dysfunction, whose characteristic is the loss in the detection, modulation or interpretation of sensory stimuli. This damage can cause inappropriate behaviors, which reduce and prevent the child's qualitative participation in pedagogical activities. In order to understand this problem, a pedagogical intervention was carried out with five children with ASD, in the process of acquiring reading and writing, in situations of low and high sensory load. The results of the research, qualitative of the type pedagogical intervention, demonstrated that it is possible to reduce the sensorial load and consequently favor the learning of the children. Thus, this article aims to emphasize the importance of the teacher considering Sensory Processing Disorder in students with ASD, in the development of pedagogical activities and in their teaching practice, in order to mitigate the losses caused by it in learning. In this context, it is highlighted that each child with ASD has a specific learning condition that requires the teacher to know new practices.